Utilization of Technology in Tourism Destination Planning: A Qualitative Analysis at Dago Dreampark Bandung - Trixie Pavella Boli; Ila Rahma Cahayani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Destination Planning and Management is now fundamentally intertwined with Digital Transformation in the Tourism Industry. Information and Communication Technology (ICT) has become a crucial strategic element in effective Tourism Planning, moving beyond a mere supporting role. This qualitative case study investigates how the nature-based destination, Dago Dreampark, integrates digital technology into its long-term planning and operational management processes. Data were collected through interviews with management, non-participant observation, and comprehensive digital media analysis (website, social media, and OTAs). The findings show that Dago Dreampark has successfully adapted the Smart Tourism concept, notably through an intensive digital marketing system. Digital technology plays a significant role in shaping the destination image and enhancing the tourist experience (smart experience). However, full strategic integration faces substantial challenges. Key issues identified include: persistent infrastructure limitations; inadequate human resources and market readiness for innovation, which was evidenced by the failed RFID wristband implementation; the need for sustained investment in technology development; and the necessity for tighter data integration to support spatial sustainability compliance. This study concludes that the strategic utilization of digital technology is an effective enabler for destination planning at Dago Dreampark, successfully elevating the tourist experience and establishing the site as a leading Smart Tourism destination in Bandung City.